Effectiveness of the progestin-only pill for migraine treatment in women: A systematic review and meta-analysis - Warhurst, Samantha; Rofe, Christopher J; Brew, Bruce J; Bateson, Deborah; McGeechan, Kevin; Merki-Feld, Gabriele S; Garrick, Raymond; Tomlinson, Susan E (Cephalalgia, 2018)
Background Migraine is highly prevalent in women (18%). Peak morbidity affects their most productive years, coinciding with peak fertility. Hormonal contraception is often tailored for migraine prevention. Estrogen-containing contraceptives may be contraindicated in women experiencing migraine with aura due to the risk of vascular events. While improvements in migraine with a progestin-only pill (POP), which inhibits ovulation are documented, the strength and quality of evidence has not been formally evaluated. Objectives To determine the effectiveness of progestin-only contraceptives for migraine treatment by systematic review and meta-analysis. Data sources and selection MEDLINE, EMBASE and Cochrane Libraries were searched (1980 to September 2016) for studies on progestin-only treatments for migraine. Studies in English on >4 non-menopausal women aged 18-50 with migraine diagnosed by formal criteria were included. Data extraction and analysis Data were quality-assessed using the GRADE system. A random effects model was used for pooled analyses. Results Pooled analyses of four studies demonstrated that desogestrel 75 mcg/day, POP significantly but modestly reduced the number of migraine attacks and migraine days. Reduced intensity and duration, reduced analgesic and triptan use were observed, along with improved headache-related quality of life. GRADE analysis indicated evidence was low to very low for each outcome measure. Adverse effects resulted in treatment cessation for <10% of participants. Two studies compared desogestrel POP to a combined oral contraceptive, demonstrating similar migraine outcomes for both treatments. Conclusions The desogestrel POP shows promise in improving migraine in women. Current evidence is observational and based on small samples of women using only one oral progestin-only formulation. Further randomized trials on additional progestin-only contraceptives are required to confirm their role in migraine management.